Jack Irish. Season 1 [videorecording (DVD)] - Dusseldorp, Marta, 1973-; Pederson, Aaron; Billing, Roy; Mailman, Deborah; Karvan, Claudia, 1972- (Acorn, 2016)
When an Australian aid-worker is kidnapped by Muslim extremists, a high-stakes race to save his life pits East against West in these exciting new episodes. From the island of Mindanao in the Philippines to Melbourne, Jack Irish is caught in a global web of religious zealotry among right-wing Christians and media-savvy jihadists.